Nurse Professionalism in Law Perspective: Risk Management of Occupational Health and Safety in the Hospital - Dewi Arradini (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Law number 38/2014 on nursing requires nurses to provide professional services. Unprofessional nurse increases health and safety risk of themselves. This study aimed to describe nursing professionalism in occupational health and safety risk management at PKU Muhammadiyah Hospital, Karanganyar, Central Java.Subjects and Method: This was a descriptive qualitative. The study was conducted at PKU Muhammadiyah hospital, Karanganyar, Central Java, from December 2018 to February 2019. There were 6 key informants selected for this study, including (1) Infection prevention and control committee, (2) Head of hospital health promotion, (3) Head division of access to hospitals and continuity of service, (4) Head of patient and family rights, (5) Head division of nursing, and (6) Head division of occupational health and safety. A sample of 50 nurses from 7 wards was selected to measure their attitude toward risk management of occupational health and safety. The study sample was selected randomly. Patients were included to describe the quality of health service from their perspective. The data were collected by structured interview and analyzed by triangulation.Results: Nursing professionalism in occupational health and safety risk management at PKU Muhammadiyah Hospital was good. In order to maintain and improve nursing professionalism, internal hospital training and regular coordination meeting were conducted, involving ward nurses and heads, and nursing committee. Occupational health and safety risks were minimal. Near-miss and accident cases were recorded and followed up for future preventive purpose.Conclusion: Nursing professionalism in occupational health and safety risk management at PKU Muhammadiyah Hospital is good. Some preventive measures had been taken to minimize occupational health and safety risk.Keywords: nursing, professionalism, risk managementCorrespondence: Dewi Arradini. School of Health Sciences Mitra Husada. Jl. Achamad Yani 167, Papahan, Tasikmadu, Karanganyar, Surakarta, Central Java. Email: dewiarra29@gmail.com. Mobile: 08994194149.Journal of Health Policy and Management (2020), 05(03): 174-179https://doi.org/10.26911/thejhpm.2020.05.03.02